دور الاستثمار الزراعي في تحقيق التنمية المستدامة من جانب البعد البيئي –دراسة حالة ولاية بسكرة- - حدانة, أ.أسماء (Recherches économiques et managériales, 2016)
الملخص:                                    إن الاستثمار الزراعي يعتبر وسيلة من الوسائل الفعالة لتحقيق التنمية المستدامة لما يحققه من مداخيل حقيقية. فالقطاع الزراعي من أهم القطاعات الواعدة في الجزائر وخاصة في ولاية بسكرة. تهدف هذه الدراسة إلى إبراز دور الاستثمار في القطاع الزراعي في تحقيق التنمية المستدامة لكن بشرط التقيد بالطرق التي تحافظ على البيئة ،ولا تؤدي إلى استنزافها وإلحاق الضرر بها. ولهذا تم التركيز على ولاية بسكرة كدراسة حالة للتعرف على واقع الاستثمار الزراعي و طرق الإنتاج المستخدمة. تزخر هذه المنطقة بمقومات فلاحية تسمح لها بتأمين متطلبات السكان من المنتجات الزراعية و تحقيق معدلات مهمة من الأمن الغذائي، كما تحتل المرتبة الأولى وطنيا في هذا المجال. بينت نتائج الدراسة أن هناك أثرين للاستثمارات الزراعية بالمنطقة. الأثر الايجابي يتمثل في خلق مناصب شغل لشباب الولاية نتيجة الزيادة في حجم الاستثمارات. أما الأثر السلبي يتعلق بالمساس بالبيئة نظرا لعدم التقيد بالقواعد الاحترازية عند استعمال المبيدات عند الزراعة .وهذا يمس بصحة الإنسان ويزيد من احتمال إصابته بمرض السرطان، واستنزاف للتربة والموارد المائية وغيرها من الأضرار الجانبية. الكلمات المفتاحية: التنمية المستدامة، الاستثمار الزراعي ، البيئة                                                     Abstract :     Agricultural investment is an efficient tool to achieve sustainable development for the real incomes that it realizes. Agricultural sector is one of the most promising in Biskra which is ranked the first nationally in agricultural production. This study aims to highlight the role of agricultural investment in sustainable development with the perquisite of respecting the rules to preserve the environment, not to exhaust and damage it. Therefore, we focused on the town of Biskra as a case study to identify the reality of agricultural investment and production methods used. This region is provided with agricultural constituents that allow it to guarantee the population's needs and realize food security, it is ranked the first nationally in this sector, too. Results of the study show that there two impacts of these agricultural investments. While the positive impact is represented in job creation for the youth of this region, the negative one is related to damaging the environment. The latter is the result of non-respecting precautionary rules when using pesticides in agriculture which affects human health and increases the possibility of cancer infection, soil and water resources exhaustion and other bad side effects. Key words : Sustainable Development, Agricultural Investment ,environment المقدمة: